2021
DOI: 10.1055/s-0041-1726126
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Early Parent Participation Program on Physiological Stability in Preterm Infants: A Randomized Controlled Trial

Abstract: Objective This research aimed to study the impact of early parent participation program (EPPP) for preterm infants in neonatal intensive care unit (NICU) on physiological instability, breastmilk feeding rates, and discharge timing. Materials and Methods Families of 147 infants born between 28 and 33 weeks' gestation were randomized at birth to EPPP group or conventional care (CC). Families in the EPPP group were trained soon after admission by using a structured education program and encouraged to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…The second significant finding of this study is that family integrated care supports breastfeeding of preterm infants, which is consistent with the previous research. In the previous studies, Pillai et al (2022) and Reiter et al (2022) reported that early parent participation in preterm infants' care facilitated a trend towards higher breastfeeding rates at discharge (Pillai et al, 2022; Reiter et al, 2022). To further analyse the reasons, we recognized that multifaceted interventions realized the positive effect of FICare on facilitating breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second significant finding of this study is that family integrated care supports breastfeeding of preterm infants, which is consistent with the previous research. In the previous studies, Pillai et al (2022) and Reiter et al (2022) reported that early parent participation in preterm infants' care facilitated a trend towards higher breastfeeding rates at discharge (Pillai et al, 2022; Reiter et al, 2022). To further analyse the reasons, we recognized that multifaceted interventions realized the positive effect of FICare on facilitating breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies are necessary to verify the conclusion.The second significant finding of this study is that family integrated care supports breastfeeding of preterm infants, which is consistent with the previous research. In the previous studies,Pillai et al (2022) andReiter et al (…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…We implement early parent participation and unrestricted visitation, albeit with strict adherence to hospital and government COVID-19 protocols. 8 The unit follows a well-known indigenously designed checklist format for high-risk newborn care commencing in the perinatal period itself (Blue book). 9 10 11 Families are prepared for the necessity for BLS training during counseling sessions close to rooming-in.…”
Section: Methodsmentioning
confidence: 99%
“…Pflegerische Elternberatende etablieren Frühinterventionen, die beispielsweise durch intensivierte Kommunikation und pflegerische Anleitung nachweislich zur Stressreduktion bei Müttern beitragen 5 711 beziehungsweise Angehörige von Patienten der Intensivmedizin entlasten 12 13 . Familienintegrierte Pflege mit Beratungsfokus führte zu besseren Ergebnissen für die Kinder 14 sowie zu psychischer Gesundheit der Eltern und höherem Wohlbefinden des Personals 15 . Ausgangsbasis dieser Entwicklungen sind die Bedarfe der Eltern, wie ein ausgeprägtes pflegebezogenes Lernbedürfnis der Mütter 16 .…”
Section: Pflegebasierte Beratung Im Familienbezugunclassified